Application of risk score analysis to low‐coverage whole genome sequencing data for the noninvasive detection of trisomy 21, trisomy 18, and trisomy 13. (23rd December 2015) - Tynan, J. A.; Kim, S. K.; Mazloom, A. R.; Zhao, C.; McLennan, G.; Tim, R.; Liu, L.; Hannum, G.; Hull, A.; Bombard, A. T.; Oeth, P.; Burcham, T.; et al.
Abstract: Objectives: Clinical performance of a low coverage, low cost, massively parallel sequencing (MPS)‐based assay to stratify risk of trisomy 21, 18, and 13 pregnancies was determined. Methods: The study included 1100 samples with birth outcome or karyotype results, comprising low‐risk patients (84.2%) negative for risk indications from maternal age, serum screening, ultrasound, or family history, and high‐risk patients (15.8%) with at least one of the aforementioned indications. Cell free DNA (cfDNA) was extracted from maternal plasma. Library preparation incorporated 96 index barcodes to enable sequencing on a HiSeq 2000 or 2500. Risk scores were calculated using chromosomal representation, fetal fraction, and maternal age at the estimated date of delivery. A risk score greater than or equal to 1 in 100 was used to stratify samples as high risk for trisomy 21, trisomy 18, or trisomy 13. Results: Sensitivity and specificity were calculated based on risk group stratification. Trisomy 21, trisomy 18, and trisomy 13 were detected with greater than 99% sensitivity and 99.9% specificity. Fetal sex classification accuracy was 99.3%. Conclusions: We conclude that simplified MPS can be used to stratify the risk of pregnancies for trisomy 21, trisomy 18, and trisomy 13 and accurately determine fetal sex. © 2015 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Whole genome sequencing of maternal plasma DNA containing maternal and fetal circulating cell free DNA can be used to detect fetal trisomy. Targeted sequencing methods can be used to risk stratify pregnancies for fetal trisomy. What does the study add? We demonstrate the performance of a low coverage whole genome sequencing method to risk stratify pregnancies for fetal trisomy 21, 18, and 13 that incorporates a combination of measured chromosomal representation, fetal fraction of the sample, and prior risk from maternal age into a combined risk score result.